Evaluation of the Allied Health Rural Generalist Program 2017‐2019. (13th May 2021) - Barker, Ruth; Chamberlain‐Salaun, Jennifer; Harrison, Helena; Nash, Robyn; Nielsen, Ilsa; Harvey, Desley; Sim, Jenny; Ciccone, Natalie; Carr, Jennifer; Bird, Katrina; Palermo, Claire; Devine, Sue
Abstract: Objective: To evaluate the development and implementation of the Allied Health Rural Generalist Program, a two‐level online post‐graduate education program, which includes Level 1, an entry‐level non‐award pathway program, and Level 2, a Graduate Diploma in Rural Generalist Practice. Design: A convergent mixed methodology evaluation in two overlapping stages: a process evaluation on quality and reach, together with a mixed method case study evaluation on benefits, of the program. Setting: Rural and remote Australia across ten sites and seven allied health professions: dietetics; occupational therapy; pharmacy; physiotherapy; podiatry; radiography; speech pathology. Participants: Process evaluation included 91 participants enrolled in all or part of the Rural Generalist Program. Case study evaluation included 50 managers, supervisors and Rural Generalist Program participants from the ten study sites. Interventions: The Allied Health Rural Generalist Program. Main outcome measures: Process evaluation data were derived from enrolment data and education evaluation online surveys. Case study data were gathered via online surveys and semi‐structured interviews. Quantitative and qualitative data were collected concurrently, analysed separately and then integrated to identify consistency, expansion or discordance across the data. Results: The Rural Generalist Program was viewed as an effective education program that provided benefits for Rural Generalist Program participants, employing organisations and consumers. Key improvements recommended included increasing profession‐specific and context‐specific content, ensuring Rural Generalist Program alignment with clinical and project requirements, strengthening support mechanisms within employing organisations and ensuring benefits can be sustained in the long term. Conclusion: The Rural Generalist Program offers a promising strategy for building a fit‐for‐purpose rural and remote allied health workforce.